L’Ovide moralisé du XIVe siècle : mort ou renaissance des Métamorphoses d’Ovide ? - Possamaï-Pérez, Marylène (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
The Ovide moralisé, anonymous poem from the beginning of the 14th century, is the first complete translation in vernacular language of Ovid’s Metamorphoses: in this sense, this text resurrects the ovidian poem, gives it life for all the lay people who did not read the latin. But this translation is for its author as the pretext for another rewrite, thematic and axiological transposition. Moreover, the “translator” often bends his source text to make it more consistent with interpretation (especially the “Christian” one) he intends to give it in a second time: can we then consider that this vernacular version makes disappear the latin poem, to replace it with another text? In fact the moralist is fascinated by his hypotexte and the phenomenon of metamorphosis: most often, he is faithful to the ovidian poetry, he describes metamorphosis in its conduct, in specifying the steps. We can say that during the 14th and 15th centuries at least, the Ovide moralisé gives life to the ovidian carmen perpetuum. In invigorating breath of the Christian spirit, the author of the Ovide moralisé metamorphosed Ovid’s poem, certainly, but saved it from death.